Modeling and simulation of an extended ASM2d model for the treatment of wastewater under different COD: N ratio. (April 2021) - Zhang, Xinhui; Nan, Jun; Liu, Tong; Xiao, Qiliang; Liu, Bohan; He, Xu; Ngo, Huu Hao; Ding, An
Graphical abstract: Highlights: An ASM2d-E-M model was established which incorporating the growth and metabolism theory of SMP and EPS. The extended ASM2d-E-M model was established to model the biological nutrient removal in the activated sludge process. A BNR system is correctly simulated under at different COD:N ratios by used of the ASM2d-E-M model. A useful tool is provided for design and optimize such systems with different influent COD:N ratios and further research. Abstract: We evaluated the impact of chemical oxygen demand (COD) to nitrogen (N) ratios on the performance of a laboratory-scale anaerobic/anoxic/oxic (A 2 O) reactor by establishing an extended ASM2d model. This extended model introduced soluble microbial products (SMPs) and extracellular polymeric substances (EPS) to create the ASM2d-E-M. Other variables were introduced in the model to describe processes that already exist in the ASM2d, and those that were previously missing (e.g. EPS/SMP). To improve the accuracy of the simulation, this study included the establishment of the model, the division of model components, a sensitivity analysis, and model calibration and verification. The average errors of COD, ammonia and orthophosphate concentrations between the steady-state simulation data and experimental data, under different COD: N ratios were 7.42 %, 13.2 % and 9.18 %, respectively. Additionally, the average errors from the EPS and SMP simulation results were lower than 1.50 % and 2.59 %, respectively. The dynamic simulation results indicate that effluent COD, ammonia, orthophosphate and biopolymer concentrations decrease with an increase in influent COD: N ratio. But orthophosphate increases when COD: N increases to 16:1. Comparing the steady-state simulation and dynamic simulation of the model with the experimental procedure confirms that the model effectively describes the biological processes in an A 2 O reactor, accurately predicts SMP and EPS production in the activated sludge system under different COD: N ratios and provides a valuable tool for the operation.